A Census of Publishers' and Booksellers' Catalogues up to 1600: Some Provisional Conclusions. - Coppens, Christian (Papers of the Bibliographical Society of America, 2008)
The article cites some provisional findings from a census of publishers' and booksellers' catalogs up to 1600. It includes an in-depth analysis of roughly 260 to 270 editions of catalogs in various categories that are included in the census, as well as a discussion on the importance of the catalogs in the reconstruction of the stock of a bookseller and the production of a publisher.